Mencetak Pengawas Tempat Pemungutan Suara Pemilihan Umum 2019 yang Sesuai Peraturan - Yohanes, Barep; Banar, Dimas Priagung (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
Bawaslu is an election management institution of the Republic of Indonesia which has the task of supervising the conduct of general elections. Panwascam is an election supervision institution that is in the sub-district level. Panwascam has the task of forming a polling station supervisor (PTPS) who has the task of overseeing elections at the polling station level. PTPS is the spearhead of Bawaslu to conduct oversight in election activities. The need for PTPS which is very difficult and more so makes Panwascam have difficulties in recruiting. The increasingly complicated performance also makes panwascam must provide a qualified understanding for PTPS when serving in polling stations. Recruitment activities through interviews and PTPS bimtek are expected to produce more competent PTPS. Through the results of the interviews, several trumpets were found regarding PTPS requirements, in this case the age of PTPS must be more than 25 years and at least high school education. Bimtek is carried out to understand PTPS about its functions, duties, and authority, and also work tools from TPS officers, and work tools used by PTPS.